GRAMMATICAL ERRORS PERFORMED BY TOURIST GUIDES IN GORONTALO CITY - Muziatun Muziatun; Ansar Tario Jusuf (Indonesian EFL Journal, 2020)
The goal of this research is to investigate grammatical errors in speaking performed by tour guides in Gorontalo city. As demanding English is a compulsory language for those who work in the tourism sector when they deal with foreign tourists. This study aims to uncover grammatical errors produced by Gorontalo tour guides. Afterwards, this research uses sequential mixed method that proposed by Creswell, which aims to investigate and discover the types of grammatical errors followed by modus data. Moreover, the data analysis of this study uses a guideline that proposed by Politzer and Ramirez who explained the types of grammatical errors in detail. This study reveals that the ability of 12 tour guides produce speaking in a grammatically low manner. It indicates that the number of grammatical errors is dominated by the verb phrase, noun phrase and transformation. Followed by third person present singular, simple past tense, and past participle. Overall, this research is expected to contribute to tour guides in Gorontalo city, especially what needs to be emphasized by tour guides in speaking grammatically.Keywords: grammatical errors; tourist guide; Gorontalo